1989
DOI: 10.3758/bf03199557
|View full text |Cite
|
Sign up to set email alerts
|

Speakers' assumptions about the lexical flexibility of idioms

Abstract: In three experiments, we examined why some idioms can be lexically altered and still retain their figurative meanings (e.g., John buttoned his lips about Mary can be changed into John fastened his lips about Mary and still mean "John didn't say anything about Mary"), whereas other idioms cannot be lexically altered without losing their figurative meanings (e.g., John kicked the bucket, meaning "John died," loses its idiomatic meaning when changed into John kicked the pail). Our hypothesis was that the lexical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
0
3

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(61 citation statements)
references
References 15 publications
(13 reference statements)
2
56
0
3
Order By: Relevance
“…The naming times were slightly faster for decomposable idiom pairs (791 msec) than for nondecomposable pairs (804) Error analyses. To ensure that the null result could not be attributed to norming disparities, we compared ratings for overlapping items in the published literature (Gibbs, 1987;Gibbs, Nayak, Bolton, & Keppel, 1989;Gibbs, Nayak, & Cutting, 1989). Of the items in the present experiment, there were six used by Gibbs and his colleagues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The naming times were slightly faster for decomposable idiom pairs (791 msec) than for nondecomposable pairs (804) Error analyses. To ensure that the null result could not be attributed to norming disparities, we compared ratings for overlapping items in the published literature (Gibbs, 1987;Gibbs, Nayak, Bolton, & Keppel, 1989;Gibbs, Nayak, & Cutting, 1989). Of the items in the present experiment, there were six used by Gibbs and his colleagues.…”
Section: Resultsmentioning
confidence: 99%
“…This solves the problem of syntactic flexibility, but raises another. Idioms vary in the extent to which they can undergo lexical manipulation without disrupting their figurative meaning (Gibbs, Nayak, Bolton, & Keppel, 1989). Wasow, Sag, and Nunberg (1983) showed that the individual parts ofsome idioms can be internally modified by the insertion of adjectives or quantifiers as in "Mary really touched a couple of nerves."…”
mentioning
confidence: 99%
“…As noted above, according to LRH idioms are mentally represented and processed as individual words, and the comprehension of decomposable and nondecomposable idioms is achieved through different processes: Decomposable idioms involve the same mechanisms of lexical retrieval and syntactic parsing taking place during the comprehension of literal expressions, whereas nondecomposable idioms require processes akin to those operating in the recognition of individual words (Gibbs, Nayak, Bolton, & Keppel, 1989). The IDH posits that only compositional expressions are fast.…”
mentioning
confidence: 99%
“…it is possible to call evidence illegally gathered "the fruit of the rotten tree", but also of the "poison tree" and even of the "poisonous tree", but in general, metaphorical expressions, like many Vol. 4(2)(2016): [165][166][167][168][169][170][171][172][173][174][175][176][177][178][179][180][181][182][183] idioms in general, often do not allow for lexical flexibility (see, for instance, Gibbs, Nayak, Bolton, & Keppel, 1989;Glucksberg, 1993: 19-23); for instance, "under" may not be replaced by "beneath" in *beneath Section XX of the Act, or "barred" may not be replaced by "prohibited" or "banned" in *time-prohibited or *time-banned. This is where two types of exercises may be prepared: the first type would be simple matching or gap-filling tasks, but also specific error prevention exercises.…”
Section: (Conflicting Laws Are Vehicles Colliding With Each Other)mentioning
confidence: 99%